Shifts and reorientation within the social-crisis and catastrophe: towards the realization of pandemic epistemological processes - Hepp, Rolf Dieter (Prekarisierung und soziale Entkopplung – transdisziplinäre Studien, 2024)
VII, 164 p. 2 illus.